A NUTRITION OVERVIEW THROUGH CENTURIES. THE PRESENT-DAY NEED OF NUTRITIONAL EDUCATION IN SCHOOLS - Simona ILAŞ (Challenges of the Knowledge Society)
The type of alimentation and the food quality of individuals has undergone remarkable changes along with the progress of the human species. This study contains an historical overview regarding human nutrition from the primitive forms until the paradoxes of contemporary alimentation. Nutritional education aims to inform and to train a person about food choices, dosage and cooking, how to identify authentic food and to understand the value of nutrition. Children need a balanced diet in order to grow and to become healthy adults. The importance of nutritional education in school is discussed taking into account the need of creating healthy eating habits which should be followed through the whole life, but also the lack of physical activity to children.